Efektifitas Pembelajaran Kontekstual Untuk Meningkatkan Prestasi Belajar Materi Luas Bangun Datar Kelas Vi Di Min Malang I - .., Suroto (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2015)
One of the causes of those unsuccessfull students is the monotonous learning model. The learning process of the concept, it cannot well associate the abstract ideas to the real world. One of the learning models that can solve this problem is the contextual learning. The procedures of the contextual learning done in this research involve the process of : (1) exploring and using the students’ concept which have been achieved by the students in the opening learning; (2) creating a study society in mastering new concepts;(3) utilization of learning medias in learning process; (4) reflction of the concepts which have been studied; and (5) testing the concept acquisition by personal student. From this results, if it use the contextual learning model,the students’ achievement will increase.Keywords: Contextual Learning, song of flt structure, various table of flt structure, Learning Achievement